Nursing quality indicators for adult intensive care: A consensus study - Evangelou, Efi; Middleton, Nicos; Kyprianou, Theodoros; Kouta, Christiana; Merkouris, Anastasios; Raftopoulos, Vasilios; Palazis, Lakis; Lambrinou, Ekaterini (My University, 2021)
Background: The selection of quality indicators demonstrating the efficiency and relevance of nursing practice in patient outcomes in the intensive care unit remains a challenge. Aim: The aim of this study was to develop a set of potential quality indicators to quantify nursing care provided to critically ill patients through a consensus method. Design and methods: This was a three-phase study including a European survey of intensive care unit (ICU) nurses (phase one) followed by a two-phase face-to-face consensus meeting of experts from Cyprus. Method: Two distinct panels of experts were asked to rate each quality indicator using a 4-point Likert scale in phases one and two. The level of consensus was set at 60%. In phase three, scores of the content validity index for items and scales were considered for the final selection of quality indicators. Results: The phase one survey included 139 ICU nurses from 13 European countries, and phases two and three included seven ICU experts from Cyprus. “Consensus in” was achieved for 12 items at the end of phase two. Three of the quality indicators were significantly different by country: (a) falls (P =.006), (b) accidental removal of nasogastric tube (P <.001), and (c) accidental removal of intravascular catheters (P <.001). Only falls was significantly correlated with higher academic qualifications of the participants (P =.002). Conclusions: Fifteen items have been identified as potential indicators for adult ICU nursing quality. These need to be prospectively studied to determine the extent to which they can accurately capture nursing care quality in this setting. Relevance to clinical practice: The study provides a set of relevant quality indicators. A nursing set for the ICU may serve as the basis for nursing management and facilitate the strategy dedicated to the vision of health care quality assurance.
Keywords: Consensus; Health care quality indicators; Intensive care unit(s); Nursing care